Multiobjective Optimization of Injection Moulding Process Parameters on Mechanical Properties Using Taguchi Method and Grey Relational Analysis - Amran Md Ali, Mohd; Idayu, Noorfa; Izamshah, Raja; Shahir Kasim, Mohd; Shukor Salleh, Mohd; ., Sivarao (International Journal of Engineering and Technology, 2018)
This study presents an optimization of injection moulding parameters on mechanical properties of plastic part using Taguchi method and Grey Relational Analysis (GRA) approach. The orthogonal array with L9 was used as the experimental design. Grey relational analysis for ultimate tensile strength, modulus and percentage of elongation from the Taguchi method can convert optimization of the multiple performance characteristics into optimization of a single performance characteristic called the grey relational grade (GRG). It is found that mould temperature of 62oC, melt temperature of 280oC, injection time of 0.70s and cooling time 15.4s are found as the optimum process setting. Furthermore, ANOVA result shows that the cooling time is the most influenced factor that affects the mechanical properties of plastic part followed by mould temperature and melt temperature.Â Â